Developing a framework for halal compliance: the case of poultry industry in Malaysia - Md Saad, Norma; Khalid, Haniza; Laluddin, Hayatullah; Hashim, Husna (2020)
This research aims to develop a framework for halal compliance in poultry processing industry. Halal status of poultry product is a major concern of most Malaysians in particular Muslim community. However, determination of halal status of poultry product involves a complex process which takes place in the industry. Many parties are believed to perform certain roles and responsibility in ensuring halal practices are strictly adhered to, thus it confirms the halal status of the product. With the motivation to understand how industry strictly conforms to the halal practices, this study will initially provide a review of the regulatory system that governs poultry activities. This will give insight on the external control available in dictating what should and shouldn’t be practiced in the industry, and what will be the legal consequence if these dictates are violated. Researcher believes that a comprehensive halal control system in the industry constitutes multiple actors or different parties, function in an integrated ways along with the formal regulatory system. With that in mind, this study will then, explore what constitutes that comprehensive halal control system, how does it functions, what are the determinants and impediments of its effectiveness. Economists usually view that any economic agent is always rational in their choice of action, including decision to follow or disregard certain rules and standards. Following this theory of rational choice, researcher will further examine what factors influence the decision to adhere (violate) halal practices among those actors directly involved in the production process in poultry processing industry. The findings of this investigation will then be meaningful for researcher to suggest a framework of halal compliance in general, and halal compliance in poultry processing industry in particular.